(3LRA aj aVd jhe YQaI heG jJYdb Hgs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3fLe GdOjf YeQ Hf eMeO Hf agO GdgGTei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JYQa Edi ChdjGFg HfYeGFg aTcQg cd ef YQag bGd Gddg YR hLd hGdaLQ hdjGd YTQ hGdTaY hGdhJQ hGdjd s
(3BNQgG (B:s
(3BNQ GdehLhO efg hCfTO HYVge dG JWjQ hSfkG Yf ebdI CfJ CgOjJ dgG WjH GdhSf s
(3HNW GdeDdas
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbW s
(3UaMI GdZdGa (B[ (3GdSWQGf GdChdGf abW (B] s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
Keywords: (3GdeLGejYs